2006
DOI: 10.1111/j.1439-0507.2006.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ABLC prophylaxis after allogeneic stem‐cell transplantation

Abstract: Invasive fungal infections (IFI) are frequent causes of mortality after allogeneic stem-cell transplantation (SCT). A very important risk factor for IFI is the use of steroids. We used a risk-based chemoprevention in an open-labelled pilot study. All patients received oral fluconazole or itraconazole (200-400 mg day(-1)) during their neutropenic episode. Starting on day +30, patients receiving prednisone > or =30 mg day(-1) were switched to twice weekly Amphotericin-B-lipid-complex (ABLC) in a dose of 4 mg kg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Several studies have shown that a single weekly high dose of lipid formulation of amphotericin B (liposomal amphotericin B) used at a dose between 7.5 mg/kg and 15.0 mg/kg was effective. Twice weekly intravenous administration of ABLC seems to be well tolerated and effective in allo-HSCT recipients treated with corticosteroids who are at high risk of IFI (20). In a recent retrospective study, highdose liposomal amphotericin B once weekly seemed effective and well tolerated for prophylaxis of IFI after GVHD in allo-HSCT recipients (37).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have shown that a single weekly high dose of lipid formulation of amphotericin B (liposomal amphotericin B) used at a dose between 7.5 mg/kg and 15.0 mg/kg was effective. Twice weekly intravenous administration of ABLC seems to be well tolerated and effective in allo-HSCT recipients treated with corticosteroids who are at high risk of IFI (20). In a recent retrospective study, highdose liposomal amphotericin B once weekly seemed effective and well tolerated for prophylaxis of IFI after GVHD in allo-HSCT recipients (37).…”
Section: Discussionmentioning
confidence: 98%
“…However, there are no sufficient data to support the use of posaconazole as prophylaxis during the initial phase after allogeneic HSCT (allo-HSCT) (18,19). ABLC, on the other hand, is an antifungal agent with broad-spectrum activity and has also been used prophylactically (20,21). Because of its intravenous formulation, ABLC could be used for antifungal prophylaxis, particularly in patients who are unable to tolerate oral medications.…”
mentioning
confidence: 99%
“…Amphotericin B lipid complex (ABLC) has been used as primary prophylaxis beyond day 30 post allograft in a cohort of patients receiving ≥30 mg prednisolone/day (55). A twice‐weekly schedule of 4 mg/kg intravenously (IV) was well tolerated, and although breakthrough fungal infection (proven and probable aspergillosis and yeast infections) occurred in 7/63 patients (11%) treated for a median of 52 days, this was considered to be effective in this high‐risk population.…”
Section: Management Peri‐transplant/chemotherapymentioning
confidence: 99%